O Empreendedor Social em África: oportunidade para o desenvolvimento da comunidade local através do turismo sustentado - Ricardo Zózimo (Cadernos de Estudos Africanos)
The number of sustainable tourism investment projects in African developing countries has grown dramatically in the last few years, motivated by the astonishing natural conditions and the demand for alternative models of tourism. The literature, however, notes that, in the majority of the cases, local communities aren’t benefiting as much as they should from this investment. This communication identifies and analyses the cultural, social and business challenges that the social entrepreneur has to go through in his quest for a profitable tourism business model that brings real development to local communities.